Pengaruh Motivasi Investasi, Pengetahuan Investasi dan Pendapatan terhadap Minat Investasi di Pasar Modal - Hutapea, Sondang R; Dewi, Gusti Ayu Ketut Rencana Sari (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
This research aims to determine (1) whether investment motivation has an affects on investment interest in the capital market, (2) whether investment knowledge affects investment interest in the capital market, (3) whether the level of income affects investment interest in the capital market. The subjects of this study were young people aged 20-45 years who have the status of residents in the Buleleng Regency. The number of respondents in this study was 347 respondents. This type of research is quantitative, with data collection using a questionnaire in the form of google form. The data analysis technique used in this research is the classical assumption test and multiple regression analysis, the coefficient of determination test, and the partial test. The results of this study indicate that (1) there is an effect of investment motivation on investment interest in the capital market, (2) there is an effect of investment knowledge on investment interest in the capital market, (3) there is an effect of income on investment interest in the capital market. The ability of the independent variable to influence the dependent variable was 41%.